The Role of Muslimah Wahdah Tanralili Branch in Da’wah Outside the Home: A Review of the Rule of al-Ḍarar al-Asyaddu Yuzālu bi al-Ḍarar al-Akhaf - Andi Dahmayanti; Munawara, Munawara; Risdayani, Risdayani; Muliana, Muliana (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2024)
This study aims to determine the role of Muslim women’s dakwah outside the home in the context of the al-Ḍarar al-Asyaddu Yuzālu bi al-Ḍarar al-Akhaf rule, with a particular focus on the activities of Muslim women engaged in dakwah outside the home. This research employs a descriptive qualitative approach, eschewing statistical analysis, and focuses on case studies derived from field research. The study employs a normative and phenomenological methodology, with a qualitative descriptive analysis. The findings revealed that the Muslimah Wahdah Islamiyah Tanralili Branch exerted a significant impact on the dissemination of da’wah in Tanralili District. Through the active organisation of religious activities in Tanralili, the Branch facilitated a gradual understanding of Islamic law among the community, enabling its practical application in their lives. With regard to the activities of Muslim women in the field of da’wah, if we consider them in the context of the rule al-Ḍarar al-Asyaddu Yuzālu bi al-Ḍarar al-Akhaf, we find that the situation of Muslim women engaged in da'wah today is one that entails certain risks. These dangers are lessened when compared to the dangers of Muslim women not preaching in the community, namely the spread of shirk and the distance of the community from Islamic law. The findings of this research imply that women are permitted to leave the house for reasons outside the home, such as preaching, but they must still adhere to the principles of modesty and decorum that are expected of them as Muslim women. They must also fulfil their domestic responsibilities before leaving the house.